Ulnar collateral ligament injury in the overhead athlete - Safran, M. R.; Hariri, S. (Clinics in Sports Medicine, 2010)
The ulnar collateral ligament (UCL), particularly the anterior portion of the anterior oblique ligament, is the primary static contributor to elbow valgus stability. UCL injuries are most common in athletes participating in overhead sports. Acute and chronic injuries to the UCL result in valgus instability, which may predispose the athlete to the development of disabling secondary elbow conditions. Provocative physical examination maneuvers include the valgus abduction test, the modified milking maneuver, and the moving valgus stress test. Plain radiographs and magnetic resonance imaging are the most common imaging modalities, although ultrasonography and computed tomography arthrograms can alternatively be used. UCL injuries can be treated initially with rest, anti-inflammatory medications, bracing, and/or physical therapy. Acute avulsion injuries can be repaired, especially in those under 20 years of age, but most UCL tears are now treated with reconstruction. Modifications of the Jobe figure-of-8 technique, and now the Altchek docking technique, are the most common reconstruction techniques. Many new and hybrid techniques have been described with limited clinical experience in the literature. Current techniques offer the athlete a greater than 90% chance of return to play at their preinjury level.